A Protein Tyrosine Phosphatase 1B Activity Inhibitor from the Fruiting Bodies of Ganoderma lucidum (Fr.) Karst and Its Hypoglycemic Potency on Streptozotocin-Induced Type 2 Diabetic Mice - Teng, Bao-Song; Wang, Chen-Dong; Yang, Hong-Jie; Wu, Jia-Sheng; Zhang, Dan; Zheng, Min; Fan, Zhao-Hua; Pan, Deng; Zhou, Ping (Journal of agricultural and food chemistry, 2011)
Inhibition of protein tyrosine phosphatase 1B (PTP1B) activity has been considered to be a promising therapy approach to treat type 2 diabetes. In this work, a novel PTP1B activity inhibitor, named FYGL (Fudan–Yueyang–G. lucidum), was screened from the fruiting bodies of Ganoderma lucidum and showed an efficient PTP1B inhibitory potency with IC50 = 5.12 ± 0.05 μg/mL. FYGL is a water-soluble macromolecular proteoglycan with a protein to polysaccharide ratio of 17:77 and a viscosity-average molecular weight (M η) of 2.6 × 105. The type 2 diabetic mice treated orally by FYGL showed an obvious decrease in plasma glucose level compared with the diabetic controls without drug treatment, comparable with that of diabetic mice treated with metformin, a clinical drug. The toxicity of FYGL is very low. The results indicate that FYGL may serve as a drug candidate or a health-care food for diabetic therapy or protection.